HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR MATEMATIKA - Maulia Isnaeni; Sandi Budiana; Mursidah Rahamah (STKIP Subang, 2023)
Maulia Isnaeni. 037117042. The Correlation of Learning Discipline with Mathematics Learning Outcomes. This study adopts a correlational approach. The subjects of this research was the fourth-grade students from Class IV A and Class IV B at Pasir Putih 01 Elementary School, Depok City, comprising a total of 72 students with a sample size of 42 students. The data collection took place during the first semester of the academic year 2021/2022. The research findings indicate a significant correlation between learning discipline with mathematics learning outcomes, as evidenced by the statistical analysis yielding a correlation coefficient (ɼxy) of 0.53. Furthermore, the coefficient of determination (KD) is calculated as 0.2809 or 28.09%. These results imply that 71.91% of the variance in mathematics learning outcomes is accounted for by factors other than study discipline. The regression equation Ŷ = 7.80 + 0.59 x indicates that an increase of one unit in study discipline is associated with a 0.59 unit increase in learning outcomes. In light of these findings, it can be concluded that there is a positive and significant corellation between study discipline with mathematics learning outcomes among fourth-grade students at Pasir Putih 01 Elementary School, Sawangan District, Depok City, during the first semester of the academic year 2021/2022.